Pengaruh Sensitivity Training dan Piecework Terhadap Peningkatan Kinerja Pada Pelaku UMKM Sate Bandeng di Kota Serang - Wahyu Ristanto; Muslim Muslim; Endang Dwi Amperawati (Amal Insani Foundation, 2023)
This study aimed to determine the effect of sensitivity training on performance improvement, the effect of piecework on performance improvement, and the effect of sensitivity training and piecework together on improving performance on Milkfish Satay UMKM in Serang City. This research uses a quantitative approach. The population in this study was 346 employees in the Sate Bandeng food processing industry group in Serang City. Samples with Slovin calculations obtained 39 samples, namely employees in the Milkfish Satay food processing industry group in Serang City. The results of this study on the first hypothesis partial sensitivity training significantly influence performance improvement, the second hypothesis, partial piecework significantly influences performance improvement, the third hypothesis, simultaneously Sensitivity Training and piecework significantly affect the performance improvement on Milkfish Satay UMKM in Serang City.